Mycoflora of Cotton Plant (Gossypium hirsutum L.) - with three New Records of Deuteromycetes from Bangladesh (Journal of Bangladesh Academy of Sciences, 2015)
Fungal diseases of cotton plant (Gossypium hirsutum L.) were studied during July, 2011 to June, 2012. Eleven cotton varieties were selected for the experiment. Alternaria alternata (Fr.) Keissler, Aspergillus niger van Tiegh, Colletotrichum gossypii Sowthworth, Colletotrichum dematium (Pers.) Grove, Curvularia clavata Jain, Fusarium sp., Gleotrichum sp., Hyalopycnis sp., Pestalotiopsis guepinii (Desm.) Stay, and a sterile fungus were isolated from infected leaves of cotton varieties CB6 and CB11. Colletotrichum gossypii was isolated from both the varieties and C. dematium was exclusively isolated from CB6. Varieties CB6 and CB11 were more susceptible than other varieties. Cotton varieties CB1, CB2, and CB3 showed negligible infection on leaves and bolls. Colletotrichum gossypii and Hyalopycnis sp. are new record for Bangladesh. Moreover, association of C. dematium, Gleotrichum sp., P. guepinii and Hyalopycnis sp. with cotton is being reported first time. The three fungi Colletotrichum. gossypii, C. dematium and Hyalopycnis sp. are described and illustrated in this account as new Deuteromycetous records for Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 213-221, 2015